Evaluating Resilience of Upland Rice to Water Stress through Study of Physiological Responses in Subtropical hills of North East India - Saikia, U.S.; Krishnappa, R.; Goswami, B.; Rajkhowa, D.J.; Ngachan, S.V. (Indian Journal of Hill Farming, 2019)
The present study sought to investigate the effects of water stress in few physiological factors,Â leaf area index (LAI) and grain yield of upland rice under rainfed subtropical hill condition ofÂ North East India. Four high yielding rice cultivars were subjected to artificially imposed water stress, of 15 days duration each, during vegetative (active tillering) and reproductive stages (grain filling) in a rainout shelter. Cell membrane stability (CMS), chlorophyll content, soil moisture, LAI and grain yield were measured. Water stress markedly increased cell electrolyte leakages in both vegetative (9.4 to 25.2%) and reproductive (12.7 to 29.6%) stages. CMS decreased with the age of the plants and the tolerant cultivars exhibited better CMS. Total chlorophyll content of water stressed plants reduced to the tune of 6.1 to 20.9% (vegetative stage) and 7.2 to 17.3% (reproductive stage). Water stress also caused drastic reduction in LAI, which ranged from 11.1 to 22.5% (vegetative stage) and 12.2 to 18.8% (reproductive stage) over the controls. The impact of water stress on physiological and growth factors of the four cultivars were reflected through differential reduction in grain yield. These results confirm that CMS and chlorophyll retention capacity are suitable indicators of water stress tolerance capability of plants and hence, screening of resilient cultivars.Â